Chronic cough: how do cough reflex sensitivity and subjective assessments correlate with objective cough counts during ambulatory monitoring?. Issue 4 (13th November 2006) - Clare Decalmer, Samantha; Webster, Deborah; Alice Kelsall, Angela; McGuinness, Kevin; Arthur Woodcock, Ashley; Ann Smith, Jaclyn
Abstract : Background: Cough reflex sensitivity, subjective estimates of cough frequency and cough-related quality of life have been used to assess cough and monitor treatment responses. The relationships between these measures and objective cough monitoring remain unclear and the usefulness of subjective assessments remains questionable. Subjects: 62 patients with chronic cough (39 women) were studied. Mean age of patients was 54.9 (SD 12.2) years, with a median duration of cough of 5.5 (range 1–30) years. Methods: Cough reflex sensitivity testing (C5; citric acid) was performed in all patients before fully ambulatory day-time and night-time cough recordings. Patients scored the frequency and severity of their cough (Visual Analogue Scales (VAS) and 0–5 score) for each recording period and completed a cough-related quality-of-life questionnaire, Leicester Cough Questionnaire (LCQ). Ambulatory cough recordings were manually counted and reported in terms of cough seconds per hour (cs/h). Cough rates were log10 transformed for analysis. Results: The median time spent coughing was 11.36 (range 1.06–46) cs/h with median day rates of 15.59 (range 2–74.8) cs/h and median night rates of 2.94 (range 0–26.67) cs/h. An inverse relationship was seen between day cough rates and log10 C5 (r = −0.452, p⩽0.001). Subjective cough scores and visual analogue scales were only moderately associated with objective time spent coughing, with night-time being scores more strongly associated than day-time scores. The strongest correlation with objective cough frequency was cough-related quality of life (LCQ), (r = −0.622, p⩽0.001), mediated through the psychological domain. Conclusions: Subjective measures of cough and cough reflex sensitivity are only moderately related to objective time spent coughing, and hence cannot be used as surrogate markers for objective cough-frequency measurements. Cough-related quality of life (LCQ) is most strongly related to objectively counted cough, and may be a useful adjunct to objective measures in the assessment of cough.